DEAD, ENCRYPTED OR STREAMED? AMERICAN FILE SHARING AND THE FUTURE OF PIRACY - Larsson, Stefan; Halbert, Debora (AoIR Selected Papers of Internet Research, 2015)
This paper inquires into the demographical characteristics, recent changes in frequencies as well as the privacy attitudes and practices of American file sharers in the social media saturated, post-Snowden world. Specifically, the paper focuses on those Americans who engaged in file sharing using the popular BitTorrent site, The Pirate Bay (TPB). In 2012 and again in 2014, TPB agreed to host a survey of its users for 72 hours. On the days in question, TPB users were directed to an on-line survey prior to entry to the website where they were asked to fill out a questionnaire. The questionnaire included questions about digital privacy and the measures taken by survey participants to engage in anonymous file sharing. In the 2012 survey there were over 96,000 respondents from all over the world, of which 18,483 stated that there were from USA, and in the 2014 survey there were over 140,000 respondents of which 29,981 stated that they were from USA.